SOCIAL MEDIA ANALYSIS OF THE PUBLIC RELATIONS DIVISION OF THE INDONESIAN NATIONAL POLICE IN THE KETUPAT OPERATION 2024 USING INTELLIGENCE SOCIO ANALYTIC (ISA) - Wobsi Prawira Sidabutar; Surya Nita; Yopik Gani (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2024)
The rapid development of information and communication technology in the digital era has significantly impacted public communication, especially through the use of social media by the Public Relations Division of the Indonesian National Police (Divhumas Polri). This study aims to analyze the effectiveness of the Intelligence Socio Analytic (ISA) used by Divhumas Polri during the 2024 Ketupat Operation in monitoring and understanding public sentiment across various social media platforms. The methodology employed is qualitative descriptive, using secondary data analysis from daily ISA reports. The findings indicate that Polri's communication strategy through social media effectively increased public positive sentiment, although challenges such as misinformation and traffic congestion still influenced some negative public perceptions. In conclusion, ISA's application by Divhumas Polri proved effective in managing public communication and maintaining societal opinion stability during the Ketupat Operation period.